1991
DOI: 10.1115/1.2920601
|View full text |Cite
|
Sign up to set email alerts
|

The Composition of Surface Layers Formed in a Lubricated Cam/Tappet Contact

Abstract: The Composition of Surface Layers Formed in a Lubricated Cam/Tappet ContactThe frictional behavior of two oils was measured in a cam/tappet friction apparatus using a direct acting bucket tappet geometry. One oil contained a soluble molybdenum friction modifier. The tappet was equipped with a removable friction disk, which allowed the frictional surface to be easily removed for surface characterization using surface profilometry, reflection infrared and XPS spectroscopies. The films consisted of varying amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…The infrared measurements suggested that there are polyphosphates in the films [6][7][8][9]. The XANES measurements have shown that the film has a bilayer structure with long chain Zn polyphosphates at the surface, and short chain polyphosphates in the bulk of the film [14][15][16]18] with little or no Fe oxide between the Fe and the phosphate due to digestion of the Fe oxide layer during phosphate formation [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The infrared measurements suggested that there are polyphosphates in the films [6][7][8][9]. The XANES measurements have shown that the film has a bilayer structure with long chain Zn polyphosphates at the surface, and short chain polyphosphates in the bulk of the film [14][15][16]18] with little or no Fe oxide between the Fe and the phosphate due to digestion of the Fe oxide layer during phosphate formation [10].…”
Section: Introductionmentioning
confidence: 99%
“…Many advanced spectroscopic techniques have been applied to elucidate the chemical nature of tribofilms generated from antiwear agents. X-ray photoelectron spectroscopy (XPS) and Auger electron spectroscopy (AES) [1][2][3][4][5], reflectance infrared spectroscopy [5][6][7][8][9] and X-ray absorption near edge structure (XANES) spectroscopy [10][11][12][13][14][15][16][17][18] have played a major role to understand the mechanisms of formation of antiwear film on the rubbed surfaces. A good summary of the role of many of these techniques is given in a very recent paper [10].…”
Section: Introductionmentioning
confidence: 99%
“…Willermet et al pioneered the use of this molecular spectroscopy on cam and tappet parts from engines (Willermet,et al (5)- (8)). It was through this research that the existence of metal phosphates on the uppermost layers of the tribofilm was definitively established.…”
Section: Introductionmentioning
confidence: 98%
“…Investigation of the film chemistry using various surface analytical techniques has shown that it is the ZDDP decomposition products and not the ZDDP itself, which provide the wear protection [5][6][7]. A number of investigations have focused on the reaction of ZDDP in solution.…”
Section: Introductionmentioning
confidence: 99%